Determining the Location of Agro-Industry Development Based on Superior Aquaculture Commodities Using Geographic Information System (GIS) - Kasid, Sri Kaidah; Bantacut, Tajuddin; Muslich, Muslich; Syamsu, Khaswar (Department of Agro-industrial Technology, University of Brawijaya, 2024)
Abstract The initial step in planning an agro-industry establishment is determining the type of superior commodities and the right industrial location. Identification of superior commodities and determination of location in coastal areas are still limited, even though the area has complex environmental conditions. This study aimed to identify superior commodities and determine potential locations for agro-industry. The research was conducted in Bekasi Regency, West Java, Indonesia. The methods used to identify advantages were Location Quotient and Shift Share. Determining industrial locations used the Geographic Information System (GIS) with the pairwise comparison method. The study results showed that the three main superior commodities in Bekasi Regency were seaweed, milkfish, and shellfish. The agro-industry potential location based on the analysis of industrial requirement parameters and by the Bekasi Regency Spatial Plan (SP) for the development of industrial areas was Cabangbungin District. The location meets the requirements in terms of proximity to energy sources, water sources, business centers/markets, accessibility to main roads, and the place's elevation and slope. The use of land cover with a potential land area by the location is 985.97 Ha. This study result can be used as a reference for policy considerations of decision-making systems for other coastal areas.Keywords: agro-industry, Bekasi Regency, GIS, leading commodities, potential location AbstrakPenentuan jenis bahan baku unggulan dan lokasi industri yang tepat merupakan langkah awal dalam perencanaan pendirian agroindustri. Identifikasi komoditas unggulan dan penentuan lokasi di wilayah pesisir masih terbatas, padahal daerah tersebut memiliki kondisi lingkungan yang bersifat kompleks. Tujuan penelitian ini adalah mengidentifikasi komoditas unggulan dan menentukan lokasi potensial agroindustri. Penelitian dilakukan di Kabupaten Bekasi, Jawa Barat, Indonesia. Metode yang digunakan untuk identifikasi keunggulan adalah Location Quotion dan Shift Share. Penentuan lokasi industri menggunakan Geographic Information System (GIS) dengan metode pairwaise comparison. Hasil penelitian menunjukkan bahwa tiga komoditas unggulan utama di Kabupaten Bekasi adalah rumput laut, bandeng, dan kerang. Lokasi potensial agroindustri berdasarkan analisis parameter syarat industri dan sesuai dengan Rencana Tata Ruang Wilayah (RTRW) Kabupaten Bekasi untuk pengembangan kawasan industri adalah Kecamatan Cabangbungin. Lokasi tersebut memenuhi syarat dalam hal kedekatan sumber energi, sumber air, pusat bisnis/pasar, aksesbilitas jalan utama, serta ketinggian dan kelerengan tempat. Penggunaan tutupan lahan dengan luasan lahan yang potensial sesuai di lokasi tersebut adalah 985,97 Ha. Hasil penelitian ini dapat dijadikan rujukan pertimbangan kebijakan sistem pengambilan keputusan untuk wilayah pesisir lainnya.Kata kunci: agroindustri, GIS, Kabupaten Bekasi, komoditas unggulan, lokasi potensial